2018
DOI: 10.1002/hlca.201800205
|View full text |Cite
|
Sign up to set email alerts
|

A Chiral Macrocyclic Oligothiophene with Broken Conjugation – Rapid Racemization through Internal Rotation

Abstract: A macrocyclic oligothiophene with an integrated pseudo‐para substituted [2.2]paracyclophane has been achieved. The synthetic sequence relies on alternating steps of halogenation‐ and Suzuki‐coupling conditions. By employing a modified Eglinton reaction under high dilution conditions, the macrocycle is closed and the obtained diacetylene is efficiently transferred to the corresponding thiophene. The molecule is fully characterized and its dynamic racemization is analyzed by variable temperature NMR experiments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…[84] Multiple regioselective halogenation and crosscoupling reactions have been used to access these macrocycles. [85] It was observed that the [2.2]paracyclophane core introduces at hree-dimensional perturbation into an early planar macrocyclic oligothiophene accompanied by macrocyclic helical chirality.…”
Section: Chiral Di-and Tetrasubstituted [22]paracyclophanes:recent Advances In Chiralityhelicityand Macrocyclizationmentioning
confidence: 99%
“…[84] Multiple regioselective halogenation and crosscoupling reactions have been used to access these macrocycles. [85] It was observed that the [2.2]paracyclophane core introduces at hree-dimensional perturbation into an early planar macrocyclic oligothiophene accompanied by macrocyclic helical chirality.…”
Section: Chiral Di-and Tetrasubstituted [22]paracyclophanes:recent Advances In Chiralityhelicityand Macrocyclizationmentioning
confidence: 99%
“…The introduction of a PC‐subunit into the framework of the macrocycle results in a helical chiral architecture. While for that purpose a twofold functionalized PC like 69 would be enough, only a fourfold substituted PC like 97 enables the decoration with bulky substituents slowing down the racemization process to a level enabling the isolation of the helical chiral enantiomers. As first model compound the macrocycle 98 exposing two para ‐(methoxycarbony)phenylethynyl substituents (Scheme ) stabilizing both enantiomers to a level, enabling their isolation was assembled …”
Section: Symmetrically Tetrasubstituted Pcs With Heterosubstituentmentioning
confidence: 99%
“…As the next step, we decided to investigate the PC building block as a helicity-inducing subunit in macrocycle 2b (Figure ). We found the helically chiral molecule to enantiomerize rapidly in solution and therefore decided to stabilize the helical chirality by mechanically hindering the racemization through strategic installation of bulky substituents …”
Section: Introductionmentioning
confidence: 99%
“…Disconnection of a C–C bond between two thiophenes in a planar oligothiophene macrocycle (Figure a,b) and attaching each of the termini to the pseudo- para -position of the top and the bottom benzene ring in PC, respectively, introduces a step in the macrocyclic ring from which the helicity of the resulting PC macrocycle emanates (Figure c,d). The oligothiophene macrocycle 2b (Figure d) comprising a pseudo- para PC step was first assembled sequentially to determine the number of thiophene subunits required to close the macrocycle . Such chiral macrocycles follow an enantiomerization process described first by Kurt Mislow as “Euclidean rubber glove”. This means that during the entire enantiomerization process the object remains chiral and achiral arrangements cannot be adopted without breaking a bond.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation